O PAPEL DA INTERNACIONALIZAÇÃO ACADÊMICA NA PÓS-GRADUAÇÃO BRASILEIRA - Stella Maris Wolff da Silva; Maria Rosa Chitolina; Ivan Rocha Neto (Instituto Federal de Mato Grosso, 2018)
Resumo: O artigo pretende analisar a criação, institucionalização e expansão da pós-graduação brasileira a partir da promulgação da Lei de Diretrizes e Bases da Educação Nacional (LDB) e da reforma do ensino superior. Igualmente, discorrerá a respeito dos esforços que as Instituições de Ensino Superior (IES) têm envidado na busca de sua internacionalização acadêmica. Durante a pesquisa, foram levantadas publicações referentes à LDB, Reforma Universitária, e internacionalização da pós-graduação brasileira com as seguintes fases de seleção: 1- Trabalho aleatório na internet para a identificação de informações científicas da área da educação; 2- Cruzamento de palavras-chave, por exemplo, reforma universitária; internacionalização da educação superior; internacionalização e globalização; 3- Identificação de periódicos científicos cujo conteúdo enunciasse a internacionalização da pós-graduação stricto sensu brasileira. A proposta da pesquisa, após a seleção das publicações, foi a de compilar e dar-lhes coesão no empenho de qualificar a pós-graduação diante da era atual. Palavras-chave: Educação. Internacionalização. Pós-graduação brasileira.   Abstract: The article intends to analyze the creation, institutionalization and expansion of the Brazilian post-graduate course after the promulgation of the Law of Guidelines and Bases of National Education (LDB) and the reform of higher education. It will also discuss the efforts that the Higher Education Institutions (IES) have been making in the pursuit of their academic internationalization. During the research, publications related to LDB, University Reform and internationalization of the Brazilian post-graduate program were collected with the following selection phases: 1- Randomized work on the Internet to identify scientific information in the area of education; 2 - Crossing of keywords, for example: university reform; internationalization of higher education; internationalization and globalization; 3- Identification of scientific journals whose content enunciated the internationalization of the stricto sensu Brazilian post-graduation. The research proposal, after the selection of the publications, was to compile and give them cohesion in the effort to qualify the graduate before the current era. Keywords: Education. Internationalization. Brazilian Post-graduation.